The Impact of the Elements of Continuous Improvement on the Quality of Work-Life - A Prospective Study in a Number of Small Industrial Organizations in the Province of Nineveh - Al –Abbadi , Dr. Shahla Salem (International Journal of Psychosocial Rehabilitation, 2020)
The study investigates the correlation and impact relationships between elements of continuous improvement and quality of work life in a number small of industrial organizations in Nineveh province thus, a hypothetical model was designed to reflect the nature of the correlations and impact between the variables based on a number of main and sub hypotheses. A questionnaire form was used by the researchers as the main tool for collecting the data besides other tools and the results were analyzed statistically to reach the study’s conclusions. In general, the research attempts to answer following the question: what is the nature of the relationship and impact between elements of continuous improvement and quality of work life in the investigated organizations? The study reached a set of conclusions including: • A significant correlation is found between elements of continuous improvement and quality of work life in the investigated organizations. • A significant impact of elements of continuous improvement on quality of work life is found in the investigated organizations. Based on the conclusions the researchers have presented a set of recommendations consistent with those conclusions and identified their method of implementation.